Alternation of psychological resilience may moderate mentalization toward mental health conditions from macro- and microstructure aspects - Chang, Yun-Hsuan; Yang, Meng-Heng; Yang, Cheng-Ta; Goh, Joshua; Lin, Sheng-Hsiang; Hsieh, Shulan (NeuroImage (Orlando, Fla.), 2024)
•Mentalization, represented by self-reflective function with stress perception level identified two clusters, hyper-mentalization, and hypo-mentalization.•Hypo-mentalization is linked to poorer mental health and lower resilience.•Neuroimaging reveals brain structural differences correlated with mentalization toward mental health conditions.•An interplay of psychological resilience and mentalization interacted with mental health conditions was observed.•The importance of balanced intrapersonal and interpersonal factors in promoting resilience correlated with mentalization. We aim to investigate the interplay between mentalization, brain microstructure, and psychological resilience as potential protective factors against mental illness. Four hundred and twenty-six participants (mean age 40.12±16.95; 202 males, 224 females), without psychiatric or neurological history, completed assessments: Dissociative Process Scale (DPS), Peace of Mind (PoM), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Resilience Scale for Adults (RSA), and Magnetic Resonance Imaging (MRI) structures with selected regions of interest, and Diffusion Tensor Imaging (DTI) maps from various tracts in the right hemisphere and connection to the frontal areas, including anterior thalamic radiation (ATR), Cingulum (hippocampus) (CH), Corticospinal tract (CST), Superior longitudinal fasciculus (SLF), Inferior fronto-occipital fasciculus (IFOF), and Uncinate fasciculus (UF) were analyzed. Two clusters, representing hypomentalization (HypoM) and hypermentalization (HyperM), were identified based on DPS, CPSS, and RFQ responses. One-way ANOVA showed no significant age or gender differences between clusters. The HypoM group exhibited lower PoM scores, higher BDI and BAI scores, and lower RSA scores (ps< 0.05). Structural brain metric comparison showed significant differences in GMV in the right caudal middle frontal gyrus (rcMFG), right superior frontal gyrus (rsFG), and right frontal pole (rFP) between groups. In addition, the HyperM individuals with a higher risk of depression and a higher ratio of intrapersonal to interpersonal factors of resilience were found with reduced GMV on the rcMFG. Additionally, analyses of DTI metrics revealed significant differences between two groups in rATR and rSLF in terms of fractional anisotropy (FA) values; rATR, rCST, rUF, rSLF, rCH and rIFOF in terms of mean diffusivity (MD) values, and radial diffusivity (RD) (corrected p = 0.05). Moreover, the positive correlation between different domains of resilience and white matter (WM) integrity implied further enhancement of intrapersonal or interpersonal resilience factors that are different for people with different mentalization. The findings underscore the importance of considering both intrapersonal and interpersonal factors in understanding the interactions between psychological resilience and mental health conditions relevant to brain mechanisms.